2008
DOI: 10.1002/jbm.a.32126
|View full text |Cite
|
Sign up to set email alerts
|

Discrete calcium phosphate nanocrystalline deposition enhances osteoconduction on titanium‐based implant surfaces

Abstract: We sought to assess the ability of nanotopographically complex titanium surfaces to accelerate osteoconduction. For this, 130 miniature bone ingrowth chambers (called "T plants"), fabricated from either commercially pure titanium (cpTi) or titanium alloy (Ti6Al4V or Ti64), with microtopographically complex surfaces were used in the study, of which 50 were further modified by the discrete crystalline deposition (DCD) of calcium phosphate (CAP) nanoparticles that superimposed a nanotopographic complexity on each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1
5

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 21 publications
4
84
1
5
Order By: Relevance
“…On the other hand, hydroxyapatite is classifi ed as a bioactive material with excellent "osteoconductive" abilities [11][12][13][14] . Osteoconduction is defi ned as bone growth on a surface that is dependent on the migration of osteogenic cells 15,16) . Osteoconduction is thus the process by which bone is directed to conform to the surface of a given material 1) .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hydroxyapatite is classifi ed as a bioactive material with excellent "osteoconductive" abilities [11][12][13][14] . Osteoconduction is defi ned as bone growth on a surface that is dependent on the migration of osteogenic cells 15,16) . Osteoconduction is thus the process by which bone is directed to conform to the surface of a given material 1) .…”
Section: Introductionmentioning
confidence: 99%
“…Anitua et al demonstrated that the incorporation of calcium ions onto the surfaces of biomaterials promoted near bone growth in rabbits' femora [12]. Similarly, other animal studies also confirmed the beneficial effects of calcium, such as improved bone formations in rat femora, increased healing of intrabony defects in dog mandibles, and enhanced resistance to dislodgement in rabbit tibia [13][14][15]. Furthermore, silica-calcium phosphate nano-composite coatings also showed improved alkaline phosphate activity of bone marrow stem cells that were attached onto the surfaces of biomaterials [16].…”
Section: Introductionmentioning
confidence: 90%
“…However, the success of orthopedic implants is also heavily dependent on a process known as osteo-integration. Previous studies have suggested that osteo-integration can be affected by various characteristics of the implant surface, such as its surface roughness, hydrophilicity, and surface chemical composition [13,[33][34][35][36][37].…”
Section: Biocompatible Surface Coatingmentioning
confidence: 99%
“…Essa influência vai dos primeiros estágios, em que superfícies mais complexas aumentam a adesão de plaquetas e fibrina (PARK & DAVIES, 2000;MENDES et al, 2009), até os estágios finais de deposição de matriz óssea, nos quais essas superfícies também favorecem a migração de osteoblastos, por meio da osteocondução (CHO et al, 2009). Assim, pesquisadores têm desenvolvido membranas com superfície interna apresentando topografia complexa, já que a que estará em contato com o defeito deverá favorecer a osteocondução e a que estará em contato com a gengiva deverá favorecer sua adesão (CHO et al, 2009).…”
Section: Perspectivasunclassified